Accessing and delivering online education in the time of COVID-19: challenges for visually impaired people in Malaysia / Andy Hickson … [et al.] - Hickson, Andy; Tajer, Leyla H.; Alobaedy, Mustafa Muwafak; Joo Vin Oh, Edmund (Faculty of Communication & Media Studies, 2023)
Researchers have found that most people doubt the capabilities of people who are visually impaired or blind. This not only disregards the voices of the visually impaired, but it can also limit access to both education and employment, while fostering stereotyping that perpetuates marginalisation. This project harnessed the capabilities of blind people as co-researchers to assist the authors investigate the unique challenges that the Covid-19 pandemic presented for visually impaired students and teachers in Malaysia. Particularly in reference to their ability to access and deliver online education; and furthermore, to identify what visually impaired students and teachers need in order to improve their online experiences. This paper explores some of the needs of visually impaired people; some of technology and applications available for visually impaired and blind learners; and provides a critique of the various forms of assistive technology currently available for visually impaired people. The researchers discovered that software and hardware exist for visually impaired learners but there appears to be a lack of training on how to use them for both students and educators. Content creator accessibility training is also lacking. Schools for visually impaired learners are not given sufficient resources and their teachers sufficient training in how to deliver effective online education. The learning of Braille is becoming a lost art form in a world that increasingly emphasizes the ‘visual’ and the translating of the visual to the non or partially sighted. The implications of this is that visually impaired learners, who already face barriers and Marginalisation are being increasingly de-skilled, under resourced and further devalued in a world where the likelihood of further pandemics and moves towards increasing use of online education is being seen as the new normal.